MONOZUKURI ASSIMILATION BEYOND JAPAN: STUDENTS’ PERSPECTIVE ON THE EFFECTIVENESS OF MONOZUKURI VALUES - Siti Rahmah Aid,; Uswah Khairuddin,; Ooi Chia Yee,; Nordinah Ismail,; Pramila Tamunaidu,; Farah Liana Mohd Redzuan, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
Monozukuri represents the fusion of craftsmanship, technological skill, and human spirit, promoting values such as pride in creation, dedication, leadership, teamwork, and continuous improvement (Thiptarajan et al., 2019; Tanaka, 2017). Although these values have been adopted within engineering programs in various countries, limited understanding exists regarding how effectively students internalize Monozukuri within their academic experiences. This study seeks to address this gap by evaluating students’ perceptions of how Monozukuri values influence their attitudes, behaviours, and approaches to learning. A validated Likert-scale survey was administered between February and April 2023 across institutions in Malaysia, Egypt, and Japan. Students provided feedback on the perceived effectiveness of Monozukuri in shaping elements such as teamwork, timeliness, leadership, and continuous improvement. The results show generally strong alignment with Monozukuri principles: students demonstrate positive teamwork attitudes, responsible management of deadlines, readiness to assume leadership roles, and a proactive orientation toward optimization. However, respondents also highlight areas for further development, particularly in proactively identifying potential problems and appreciating diversity in team composition. Overall, the study indicates that while Monozukuri values are reflected in student attitudes, strategic reinforcement is needed to enhance problem-solving initiative and foster inclusivity within collaborative engineering environments.